Pengaruh Biaya Operasional terhadap Pendapatan Operasional dan Capital Adequacy Ratio terhadap Financing to Deposit Ratio pada Bank Umum Syariah di Indonesia - Fuji Hartati Jaenudin; Syifa Salsabila; Yani Aguspriyani (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2026)
This study aims to analyze the effect of Operating Costs to Operating Income (BOPO) and the Capital Adequacy Ratio (CAR) on the Financing to Deposit Ratio (FDR) of Islamic Commercial Banks in Indonesia during the 2021–2025 period. The study uses an associative quantitative approach utilizing quarterly time series data obtained from Islamic Banking Statistics published by the Financial Services Authority. Data analysis was performed using multiple linear regression using STATA software, with the Cochrane-Orcutt method applied to address autocorrelation. The results reveal three main findings. First, BOPO has a negative and significant effect on FDR at the 10% significance level. This indicates that increased operating expenses can limit banks' ability to disburse financing. Second, CAR has no significant effect on FDR. This finding indicates that a high level of capital adequacy does not directly drive increased financing, reflecting banks' prudent attitude in the post-pandemic period. Third, BOPO and CAR simultaneously have a significant effect on FDR. Based on these results, this study concludes that operational efficiency has a more dominant role in explaining the intermediation function of Islamic Commercial Banks compared to capital adequacy.